Peningkatan Pemahaman Nilai-Nilai Pancasila Berbasis Model Bruce and Weil dalam Pembelajaran IPA di Sekolah Dasar - Syiti Mutia Hasnan; Arita Marini; Linda Zakiah; Riswandi (Postgraduate, University of Mataram, 2024)
This study aims to improve students' understanding of Pancasila values in science learning in elementary schools by applying Bruce and Weil's learning model, especially the Social Interaction Model, which emphasizes the importance of cooperation and discussion. The research was conducted on grade IV students at SDN 19 Kampung Baru Kota Pariaman using the experimental method and Static Group Comparison design. Two groups were involved: an experimental class that applied the Bruce and Weil model, and a control class that used the conventional lecture method. Data were collected through learning outcome tests and analyzed statistically. The results showed that the application of the Bruce and Weil model had a significant effect on improving the understanding of Pancasila values. The average posttest score of the experimental class was 85, while the control class reached 70. Hypothesis testing resulted in a tcount of 22.70, greater than the ttable of 1.68 at the 0.05 significance level, so the alternative hypothesis (Ha) was accepted. Bruce and Weil's model proved effective in improving the understanding of Pancasila values through active participation of students in science learning. This model is recommended as an effective alternative to integrate Pancasila values in science learning in elementary schools.